(untitled) (Research, Society and Development, 2024)
Malaria remains a public health concern in Mozambique. In 2015, it accounted for 29% of all hospital deaths and 42% of deaths in children under 5 years old. Understanding the factors behind malaria cases has been subject to debate in various fields of knowledge. However, there is a critical gap in information related to social and cultural factors, where the perceptions that social actors have about malaria are not part of a priority research agenda. Taking this scenario into account, the present study aimed to describe the perceptions that social actors from Govuro, in the province of Inhambane, have about malaria and how these influence the registration of cases of this disease. The data collection consisted of open interviews with 25 research subjects selected intentionally and for convenience. The methodology used was a qualitative approach based on phenomenology. The results show that malaria is perceived by social actors as it is institutionally conveyed. However, due to economic and social realities as well as the belief that malaria is inevitable, there is a lack of consistency between how it is perceived and how action is taken to address it, hence the registration of cases of this disease.